PENGEMBANGAN USAHA KECIL MENENGAH DI INDONESIA MELALUI PERAN BANK SYARIAH - Eddy Suratno (J-MAS (Jurnal Manajemen dan Sains), 2017)
Indonesia  is  one  of  the  countries  of  the  third  world  countries  are  categorised  are  still  in  the  developing  stage.  In  the  context  of  developing  countries,  the  system  state  economy  often  rely  against  capital  assistance  from  outside  the  country.  This  has  a  lotof  bearing  controversial  in  a  country  life  order.  On  the  pretext  of  collaboration  withforeign  parties  in  relation  to  capital  assistance  to  help  grow  the  economy  of  the  country,  it  was  important  for  this  pretext  away  from  the  purpose  originally,  the  contraryhas  been  spoiling  the  nation  own  to  keep  dependent  against  help-the  help  is  always  given  by  the  outside  parties  to  us,  so  that  we  can  feel  the  implication  itself  i.e.  the  lack  of  independence  of  the  US  to  build  our  own  nation.  The  crisis  that  hit  the  nation  of  Indonesia  has  had  floods  in  all  joints,  including  the  banking  sector  lives  also  on  view  as  one  trigger,  i.e.  with  credit-credit  disalurkannya  the  wrong  target.  The  crisis  proved  that  the  number  of  small  and  medium  businesses  are  very  much  able  to  survive  the  crisis  facing  independently.  While  the  economy  has  now  started  shows  stretching  to  bounce  back,  it  seems  as  if  the  medium-small  business  back  into  oblivion,  especially  with  many  entry  and  operation  of  foreign  businesses  –  including  foreign  sales  period  of  post-war  banking  assets  national  banking.  Islamic  banking  which  has  been  established  since  the  year  1992  apparently  can  now  be  renewed  hope  for  the  small  and  medium  enterprise  development,  especially  in  the  procurement  of  working  capital.Keywords:  Islamic  Banking,  Small  Business